Academic Anxiety among Primary School Students - Rajesh Rathod; Dharmik Chauhan (MASI Mandiri Edukasi, 2023)
The main objective of the present research was to study the academic anxiety of Gujarati and English medium primary schools in Gandhinagar City. The study population was the Gujarati medium and English medium school students of Gandhinagar City. With the help of the Random Sampling technique, Gandhinagar City was selected from four taluka, and the researcher selected 200 students from six English medium and 200 students from six Gujarati medium primary schools. A total of 400 students were selected as a sample, of which 100 boys and 100 girls were taken from Gujarati medium Primary school, and 100 boys and 100 girls were taken from English medium Primary school. In this study, the researcher used the survey method of research. The Academic Anxiety Scale for Children (AASC), developed and standardized by Singh, A.K.Â and Dr. A. Sen Gupta, will be used for measuring academic anxiety was used for research. Collected data were analyzed by t-test. Both medium students have the same academic anxiety, or we can say there is no academic anxiety in both medium students. Nevertheless, Gujarati medium students have more academic anxiety than English medium students. Gujarati medium girlâ€™s students have more academic anxiety than English medium girlâ€™s students.